Intracerebral Hemorrhage Post-COVID 19 Infection - Khalid W. Al-Quliti, Rakan M. Alhujeily, Obaid M. Aljarbou (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COVID 19, which can lead to neurological complications including intracerebral hemorrhage (ICH), has caused a challenging worldwide pandemic. We aim to highlight the clinical, radiologic and laboratory characteristics, as well as functional outcomes of patients with COVID-19, who either presented with ICH or subsequently developed ICH. Methods: Related PubMed articles and studies on ICH and COVID-19 (published from January 2020 to October 2021, were searched. Our inclusion criteria included all articles written in English, involving COVID-19 patients confirmed via PCR test and admitted to hospital or ICU, and large ICH on neuroimaging. Results: We collected 23 published studies with an association between COVID-19 and ICH, focusing on the clinical profile, neuroimaging findings and management. The risks for ICH includes comorbidities like hypertension, diabetes, chronic kidney disease and malignancy, and anticoagulation therapy. In one study parenchymal haemorrhages with mass effect and herniation showed a very high mortality rate and most of those patients received either a therapeutic or prophylactic dose of anticoagulates prior to ICH discovery. Conclusion: ICH and COVID-19 are rare but with high morbidity and mortality. Thus, it is important to recognize early those patients at high risk of having ICH, mainly those patients with comorbidities and on anticoagulation therapy, to improve health care outcomes.